(untitled) (Bodhi Path, 2024)
The legends surrounding the Buddha’s conception and birth, including the one about Māyā’s dream, are richly detailed in Pāli literature. This particular legend is extensively mentioned in the Mahāpadāna Sutta (Dīgha Nikāya.14), the Acchariyabbhūtadhamma Sutta (Majjhima Nikāya.123), and the Nidānakathā. The legend, depicted in the Bhārhut sculptures and on display at the Kolkata National Museum, suggests a magical and immaculate conception of the Buddha. In this narrative, the Buddha’s conception is not a result of ordinary human reproduction but is presented as a miraculous event. The symbolism of the six-tusked white elephant is crucial in this legend, as it plays a significant role in the conception. According to the account, the white elephant enters the body of Māyā, the Buddha’s mother, through her right rib in a dream.